(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this study is to analyse whether the aid projects provided by Korea to Azerbaijan have been able to meet the national demand of Azerbaijan. It thereby aims to contribute to the development of a methodology that can evaluate whether Korean ODA projects meet the national demands of the recipient country. Secondly, it sets out to determine to what extent Korean ODA projects for Azerbaijan, which to date have not been the subject of academic study, are suited to that country’s needs. This research thus seeks not only to assist research on other countries in the future, but also to contribute to efforts to improve the suitability of the recipient country’s demand for Korean ODA..